2013
DOI: 10.5489/cuaj.993
|View full text |Cite
|
Sign up to set email alerts
|

Effect of detrusor overactivity on the expression of aquaporins and nitric oxide synthase in rat urinary bladder following bladder outlet obstruction

Abstract: E268research research AbstractBackground: Aquaporins (AQPs) have recently been reported to be expressed in rat and human urothelium. Nitric oxide (NO) is thought to play a role in the bladder overactivity related to bladder outlet obstruction (BOO). The purpose of this study is to investigate the effect of BOO on the expression of AQP2-3 and nitric oxide synthase (NOS) isoforms in rat urothelium. Methods: Female Sprague-Dawley rats (230-240 g, n = 60) were divided into 2 groups. The control group (n = 30) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Furthermore, changes in the detrusor muscle innervation and muscle structure have been found. Recently also potassium channels decrease, ischemic‐induced changes and the nitric oxide pathway changes were found . Barbosa et al compared bladder histology between patients undergoing TURP vs non‐obstructed control patients and found upregulations of collagen types I and III.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, changes in the detrusor muscle innervation and muscle structure have been found. Recently also potassium channels decrease, ischemic‐induced changes and the nitric oxide pathway changes were found . Barbosa et al compared bladder histology between patients undergoing TURP vs non‐obstructed control patients and found upregulations of collagen types I and III.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous report, detrusor overactivity caused by BOO led to a significant increase in the expression of AQP2–3, and nitric oxide synthase (endothelial nitric oxide synthase, neuronal nitric oxide synthase) in rat urinary bladder. In the study, we suggested that the AQPs and nitric oxide synthase isoforms might have a specific role in bladder dysfunction that is related with bladder change following BOO [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous reports, we demonstrated altered expression of AQP1 in the urinary bladder of rats presenting detrusor overactivity [ 12 - 14 ]. Further, in a more recent study, we speculated about the relation between AQP1 and CAV1 in the urinary bladder, and found that they are significantly overexpressed upon detrusor overactivity (caused by bladder outlet obstruction [BOO]).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…By finding no significance after addition of vardenafil, the authors postulated that increase of guanylate cyclase was the main target for nitric oxide/cyclic guanosine monophosphate pathway. In another study using the same experimental model, Kim et al [31] have shown a significant increase of endothelial nitric oxide synthase and neuronal nitric oxide synthase in rats with induced bladder outlet obstruction. The same authors reported an increase of the expression of aquaporin2-3, which is also involved in the nitric oxide pathway.…”
Section: Underlying Pathophysiology Of Overactive Bladder In a Contexmentioning
confidence: 95%